Applying the POUR Model to Enhance Digital Accessibility in HyFlex Learning Environments - Nussli, Natalie; Oh, Kevin (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2025)
The purpose of this study is to advance the accessibility of a hybrid-flexible (HyFlex) learning environment by applying the four attributes of the POUR model (WCAG 2.1, 2018), namely, perceivable, operable, understandable, and robust, to make digital learning content more accessible to all learners. The connections between the POUR principles and the principles of four frameworks instrumental to digital accessibility––Universal Design, Universal Design for Learning, Mobile Seamless Learning, and HyFlex––are discussed. The study describes one educator’s journey to learn the core skills of making learning resources more accessible to undergraduate students at a teaching university in Switzerland. Qualitative data was obtained from a focus group involving three students, as well as from an external evaluator who conducted a digital accessibility check based on commonly used accessibility criteria. This revealed that the criteria were implemented with varying effectiveness. Findings from the focus group suggest that the instructor’s efforts to increase digital accessibility were noticeable. Obstacles were mainly related to navigation issues and the different participation modalities integral to HyFlex. The study offers practical advice for instructors who wish to increase digital accessibility and adaptability in their courses.